Advances in research on potential therapeutic approaches for Niemann-Pick C1 disease - Zhang, Caifeng; Su, Keke; Jiang, Xu; Tian, Yuping; Li, Ke (Frontiers in Pharmacology, 2024)
Niemann-Pick disease type C1 (NP-C1) is a rare and devastating recessive inherited lysosomal lipid and cholesterol storage disorder caused by mutations in the NPC1 or NPC2 gene. These two proteins bind to cholesterol and cooperate in endosomal cholesterol transport. Characteristic clinical manifestations of NP-C1 disease include hepatosplenomegaly, progressive neurodegeneration, and ataxia. While the rarity of NP-C1 disease presents a significant obstacle to progress, researchers have developed numerous potential therapeutic approaches over the past two decades to address this condition. Various methods have been proposed and continuously improved to slow the progression of NP-C1 disease, although they are currently at an animal or clinical experimental stage. This overview of NP-C1 therapy will delve into different theoretical treatment strategies, such as small molecule therapies, cell-based approaches, and gene therapy, highlighting the complex therapeutic challenges associated with this disorder.